Clinical and metabolic characteristics in hidradenitis suppurativa - An Indian perspective - Vibhu Mendiratta; Vidya Yadav; Apoorva V Bhardwaj; Rashi Pangti (Wolters Kluwer Medknow Publications, 2023)
Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory, recurrent follicular disorder affecting apocrine gland bearing areas such as axillae, inframammary area and groin. Significant association of HS with metabolic derangements such as hypertension, obesity, hyperlipidemia and hyperinsulinemia has been found. There is dearth of literature on epidemiological and metabolic profile of HS in Indian subjects. Aim: The aim of this study is to assess abnormalities in the levels of fasting blood glucose, serum insulin, and lipid profile in patients with HS. Primary Objective: To assess the frequency of abnormal levels of fasting blood sugar, serum insulin and lipid profile in patients with HS. Secondary objectives: To assess the frequency of hypertension, raised basal metabolic index, polycystic ovarian syndrome, follicular disorder, erythrocyte sedimentation rate (ESR) and c-reactive protein (CRP) in patients with HS and to assess the severity of of clinical presentation HS using Hurley staging system. Methodology: This is a retrospective record based study. Records of clinically diagnosed patients of HS, aged > 18 years fulfilling the inclusion and exclusion criteria were analysed. Results: Total 30 patients were recruited with 1:1 male to female ratio. Five (16.67%) cases fulfilled NCEP ATP III criteria for the diagnosis of metabolic syndrome. Statistically significant association was observed between severity of HS, in younger age group (<20 years), moderate to severe BMI, fasting serum insulin, fasting total cholesterol and raised ESR. Limitations: This is retrospective, hospital record based study with small sample size. Conclusion: Holistic management of HS should be individualized according to need of patient and it should be combined approach including dermatologist, plastic surgeon, psychiatrist and dietician. We recommend an initial screening for derangements in metabolic profile in these patients for more effective management and preventing long term cardiovascular complications.